Excitation-energy dependence of the fission-fragment neutron-excess ratio; Physical Review C; Vol. 107, iss. 2 - Pasca H. Horia; Andreev A. V. Aleksandr Vasiljevich; Adamian G. G. Gurgen Grigorjevich; Antonenko N. V. Nikolay Viktorovich (2023, 2023)
Title screen